Грамматология формы: знак – текст – произведение - Стамати, В.В. (Культура народов Причерноморья, 2014)
В статье рассматривается категория формы как лингвистический момент
литературного произведения, ввиду чего она не может быть осмыслена как активная ценностная
деятельность, а значит, стать объектом эстетического восприятия. В связи с этим выдвигается и
обосновывается тезис о принципиально ином способе координации формы и содержания – по типу
отношений означающего (организационного аппарата формы) и означаемого (произведения как
результата монолинейного прочтения текста). У статті розглядається категорія форми як лінгвістичний момент літературного твору,
через що вона не може бути осмислена як активна ціннісна діяльність, а отже, постати об’єктом
естетичного сприйняття. У зв’язку з цим висувається та обґрунтовується теза про принципово інший
спосіб координації форми та змісту – за типом відношень означника (організаційного апарату форми)
та означуваного (твору як результату монолінійного прочитання тексту). In the article a category of form as linguistic moment of literary work is considered for which reason
it cannot be comprehended as a value activity and cannot become an object of aesthetic perception. In this
connection thesis about relations between form and substance by analogy relations between signifier
(organizational apparatus of form) and signified (literary work as a result of monolinear reading of the text) is
brought up and based. The aim at the difference between compositional and substantial sides of form inevitably
leads to the analysis of linguistic material and projecting the results in the sphere of substance, and investigation
is reduced to detection of genetically related story structures based on the exposure of which the erroneous
conclusion about substantiveness of form is brought up. As a result, the form cannot be the object of aesthetic
perception because it only performs organizing function but without losing its ontological potential: volitional
tension of form finds itself in a gesture that organizes language material and which defines one or another type
of relations between the components of the text. It leads to the fact that “a text” is read as “the literary work”.